Protein-nucleotide contacts in the immunoglobulin heavy-chain promoter region. - Landolfi, N F (1987)
Immunoglobulin heavy-chain variable-region genes contain the octanucleotide ATGCAAAT upstream from the site of transcription initiation. The complement of this sequence, in the reverse orientation, is found at an identical location in light-chain variable-region genes. This sequence element is thought to be involved in the lymphoid-specific expression of immunoglobulin genes. Analysis of nuclear extracts from both lymphoid and nonlymphoid cells in a gel migration inhibition assay, using an immunoglobulin promoter region fragment containing the octamer, reveals multiple migration-retarded species that represent specific DNA-protein complexes. The number and relative level of these complexes vary with cell type; some complexes are detected with all extracts, whereas one complex is lymphoid-specific and may represent an interaction involved in the lymphoid-restricted expression of immunoglobulin genes. Mitogenic stimulation of a B-lymphoid line can increase the level of the protein responsible for this lymphoid-specific complex. Analysis of the complexes detected in the gel migration inhibition assay by DNase I protection ("footprinting") has revealed that all of these DNA-protein complexes involve contact of the protein with the nucleotides of the octamer. One complex, present in both lymphoid and nonlymphoid cells, displays an additional DNA-protein contact adjacent to the octamer. Our results also indicate that the interaction of proteins with the octameric sequence can cause a local alteration in the structure of the DNA helix.